Educational Research Articles PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) UNTUK MENINGKATKAN HASIL BELAJAR IPA - Jasicca Dea Putri Perwiranti; Habiddin Habiddin; Rudiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve students’ academic performance in Science through the application of the Culturally Responsive Teaching (CRT) approach among eighth-grade students at SMP Sriwedari. The research employed a Classroom Action Research (CAR) methodology, conducted in two cycles. Each cycle consisted of the stages of planning, implementation, observation, and reflection. Data were collected using formative tests and observations of student activities during the learning process. The findings revealed a significant improvement in students’ learning outcomes across the cycles. Prior to the intervention (pre-cycle), the student mastery level was only 33.33%. After implementing the CRT approach, the mastery level increased to 66.67% in the first cycle and further rose to 88.89% in the second cycle. These results indicate that CRT is effective in enhancing science learning outcomes and fostering active student engagement by connecting instructional content to their cultural and environmental context.